Serum erythropoietin levels in patients wıth severe anemıa secondary to inflamatorybowel dısease and the use of recombinant human erytropoietin in patıents with anemia refractory to treatment - Levent DEMİRTÜRK; Saadeddin HÜLAGÜ; Mustafa YAYLACI; A. Kemal GÜRBÜZ; Mehmet ALTIN; Melih ÖZEL; Ali ÖZCAN (Turkish Journal of Gastroenterology, 2020)
-